Analysis of Student Responses at MA Al-Djufri to the Use of PhET Media as a Virtual Laboratory for Electromagnetic Induction - Mahrus, Mahrus; Hasanah, Nurul; Jailani, Abdul Qodir; Ibana, Lukluk (Lombok Institute, 2024)
This study aims to analyze student responses to using the PhET simulation application in electromagnetic induction laboratories at MA Al-Djufri Blumbungan. A descriptive quantitative methodology was employed, with data collected through a survey using a questionnaire that gathered written verbal feedback from 17 twelfth-grade science students. The findings indicate that the PhET application was well-received by students and proved beneficial in enhancing their understanding of electromagnetic induction through virtual laboratories. Over 83% of the students agreed or strongly agreed on the effectiveness of the PhET application in the laboratory, demonstrating a high acceptance of this learning medium. This research supports the integration of virtual laboratories in science education as an effective way to improve student learning experiences and develop their conceptual understanding.